Effectiveness of home based exercise program taught by physiotherapist on pain and function in knee osteoarthritis - Yılmaz, Merve; Şahin, Mustafa; Algun, Zeliha Candan (Springer London Ltd, 2018)
[Abstract Not Available]
WCO-IOF-ESCEO World Congress on Osteoporosis, Osteoarthritis and Musculoskeletal Diseases -- APR 19-22, 2018 -- Krakow, POLAND
WOS: 000440102403235
Keywords: Knee Osteoarthritis; Physiotherapy; Home Exercise; Exercise Education